A Comparison between Collaborative and Authoritative Leadership Styles of Special Education Administrators - Veale, Natasha W. (Journal of the American Academy of Special Education Professionals, 2010)
Supervisors, administrators, and directors of special education usually use the authoritative leadership style when supervising their special education staffs; however, collaborative leadership styles are slowly overtaking authoritative leadership styles. These leaders have the task of producing an environment where the culture is inclusive, the relationships are positive, and partnerships are developed and responsible for the success of all students with disabilities Managing strictly by objectives could produce a close-minded type of system that could produce an unpleasant environment, making it difficult for special education teachers to do their jobs efficiently. In this article, the author compares and contrasts the collaborative leadership style with the authoritative leadership style amongst special education personnel in leadership positions. A review of literature determines utilizing a more collaborative leadership style is successful at increasing special education staff productivity.